Nurses’ attitudes towards family presence during the management of an acutely deteriorating patient in the emergency department - Mabetshe, Lindokuhle (My University, 2020)
Background: Families are essential to the holistic wellbeing for many hospitalized patients. Patient care is mostly done by nurses in the emergency department. Research over the last three decades has focused on family presence during resuscitation and yet little is known about the presence of family during the management of an acutely deteriorating patient. Objectives: To describe Nurses’ attitudes towards family presence during the management of an acutely deteriorating patient in the emergency department. Methods: A descriptive quantitative study was done in the emergency departments of three tertiary hospitals in Eastern Cape. Professional nurses (n=57) in three emergency departments in Eastern Cape, South Africa completed a 13-item Emergency Department Family Presence survey that was published in Emergency Nursing Journal. Data was analysed using univariable and multivariable logistic regression for these outcomes; Effect on patient care, Effect on the patient, Effect on the family and Effect on the individual healthcare provider. Results: Most nurses believed that family presence during the management of an acutely deteriorating patient has negative effects on the patient, on the family and on the healthcare providers. Significance was only seen with increased years of experience.Conclusions: family presence during the management of an acutely deteriorating patient is a new concept in South Africa. Therefore, nurses do not hold strong views about it yet, hence, the negative attitudes towards it.
A research report submitted in partial fulfillment of the requirements for the degree of Master of Science in Nursing to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2020